2007
DOI: 10.1038/nature06030
|View full text |Cite
|
Sign up to set email alerts
|

LKB1 modulates lung cancer differentiation and metastasis

Abstract: Germline mutation in serine/threonine kinase 11 (STK11, also called LKB1) results in Peutz-Jeghers syndrome, characterized by intestinal hamartomas and increased incidence of epithelial cancers. Although uncommon in most sporadic cancers, inactivating somatic mutations of LKB1 have been reported in primary human lung adenocarcinomas and derivative cell lines. Here we used a somatically activatable mutant Kras-driven model of mouse lung cancer to compare the role of Lkb1 to other tumour suppressors in lung canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

64
985
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 927 publications
(1,077 citation statements)
references
References 35 publications
64
985
2
1
Order By: Relevance
“…We and others had previously shown that Crtc1 is a bona fide cancer gene when activated by a t(11;19) chromosomal translocation resulting in the aberrant transcription of certain Crtc1 inducible genes, including the orphan nuclear receptor NR4A2 (Tonon et al, 2003;Coxon et al, 2005;Wu et al, 2005). As LKB1 has been identified as a key regulator for Crtc2 transcriptional activity (Shaw et al, 2005;Katoh et al, 2006) and because somatic mutations have been identified in a subset of human lung tumors and cell lines (Sanchez-Cespedes et al, 2002;Ji et al, 2007), our data now suggest that enhanced Crtc gene family activity may participate in the tumorigenic process within LKB1 null tumors that are not otherwise associated with the recurrent t(11;19) rearrangement. Interestingly, overexpression of NR4A2 had been previously reported for HeLa and H460 cell lines, which are both known to be LKB1 null (Tiainen et al, 1999;Katoh et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…We and others had previously shown that Crtc1 is a bona fide cancer gene when activated by a t(11;19) chromosomal translocation resulting in the aberrant transcription of certain Crtc1 inducible genes, including the orphan nuclear receptor NR4A2 (Tonon et al, 2003;Coxon et al, 2005;Wu et al, 2005). As LKB1 has been identified as a key regulator for Crtc2 transcriptional activity (Shaw et al, 2005;Katoh et al, 2006) and because somatic mutations have been identified in a subset of human lung tumors and cell lines (Sanchez-Cespedes et al, 2002;Ji et al, 2007), our data now suggest that enhanced Crtc gene family activity may participate in the tumorigenic process within LKB1 null tumors that are not otherwise associated with the recurrent t(11;19) rearrangement. Interestingly, overexpression of NR4A2 had been previously reported for HeLa and H460 cell lines, which are both known to be LKB1 null (Tiainen et al, 1999;Katoh et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…As a major upstream regulator of AMPactivated protein kinase subfamily members, including MARK/Par-1, LKB1 is involved in multiple aspects of cell function and has been linked to many human diseases especially malignant tumors. [63][64][65][66][67][68][69][70][71] Recently, LKB1 has been implicated in B-cell differentiation by mediating activation-induced cytidine deaminase-dependent remodeling of immunoglobulin genes, 72 as well as in T-cell differentiation by regulating TCR-mediated activation of phospholipase C gamma1 and AMP-activated protein kinase signaling. 73,74 LKB1 is directly phosphorylated by lymphocyte-specific protein tyrosine kinase and predominantly interacts with the adaptor protein LAT as well as phospholipase C gamma1 following TCR stimulation.…”
Section: Gck-iii Kinases As Immerging Novel Immune Regulatorsmentioning
confidence: 99%
“…Mutational analysis across a range of sporadic tumors has identified loss of function LKB1 mutations most frequently in non-small cell lung carcinomas; between 5 and 17% of cases depending on the population studied (Sanchez-Cespedes et al, 2002;Ji et al, 2007;Koivunen et al, 2008). Somatic inactivating mutations in LKB1 have also been reported in approximately 5% of pancreatic cancers and melanomas, and in single specimens of prostate cancer and cervical cancer (Avizienyte et al, , 1999Bignell et al, 1998;Wang et al, 1998;Guldberg et al, 1999;Rowan et al, 1999;Su et al, 1999;Forster et al, 2000;Ikediobi et al, 2006).…”
Section: Peutz-jeghers Syndrome and Human Cancer Geneticsmentioning
confidence: 99%